Strengthening Legal Literacy and Democratic Citizenship through an Advocacy-Based Approach in Civic Education - Sukron Mazid; Giri Harto Wiratomo; Hartutik Hartutik; Novitasari Novitasari; Atsani Wulansari; Eem Munawaroh (Indonesian Journal of Advocacy and Legal Services, 2026)
This study aims to analyze the strengthening of synergy between legal literacy and democracy through the integration of legal advocacy and civic education. This study is grounded in the weak legal awareness of citizens, the lack of critical participation in public affairs, and the limited comprehension of constitutional rights and obligations among the younger generation. This research applied a descriptive qualitative approach through literature studies, normative analysis, and case studies. The data was obtained from literature, interviews, and participatory observations. Thematic analysis was conducted to examine the synergy of legal advocacy and civic education and to explore its effects on legal literacy, civic consciousness, and democratic participation within schools and the wider community. The findings indicated that legal advocacy serves not only as a mechanism for right protection, but also as a pedagogical medium for internalizing the values of democracy, justice, and active citizen participation. The integration of legal advocacy in Civic Education can strengthen civic knowledge (legal and civic knowledge), civic skills (critical thinking, advocacy, and problem solving), and civic disposition (democratic attitudes, social responsibility, and concern for justice). In conclusion, legal advocacy–based civic education can foster citizens who, beyond understanding their rights and obligations, also demonstrate the courage and capacity to advance public interests within a democratic framework.